Recent Research Progress: Discovery of Anti-Plant Virus Agents Based on Natural Scaffold - Chen, Jixiang; Luo, Xin; Chen, Yifang; Wang, Yu; Peng, Ju; Xing, Zhifu (Frontiers in Chemistry, 2022)
Plant virus diseases, also known as “plant cancers”, cause serious harm to the agriculture of the world and huge economic losses every year. Antiviral agents are one of the most effective ways to control plant virus diseases. Ningnanmycin is currently the most successful anti-plant virus agent, but its field control effect is not ideal due to its instability. In recent years, great progress has been made in the research and development of antiviral agents, and the mainstream research direction is to obtain antiviral agents or lead compounds based on structural modification of natural products. However, no antiviral agent has been able to completely inhibit plant viruses so far. Therefore, the development of highly effective antiviral agents still faces enormous challenges. Therefore, we reviewed the recent research progress of anti-plant virus agents based on natural products in the past decade, and discussed their structure-activity relationship (SAR) and mechanism of action. It is hoped that this review can provide new inspiration for the discovery and mechanism of action of novel antiviral agents.